2019
DOI: 10.3389/fpls.2019.01419
|View full text |Cite
|
Sign up to set email alerts
|

Xylem Cell Wall Formation in Pioneer Roots and Stems of Populus trichocarpa (Torr. & Gray)

Abstract: Regulation of gene expression, as determined by the genetics of the tree species, is a major factor in determining wood quality. Therefore, the identification of genes that play a role in xylogenesis is extremely important for understanding the mechanisms shaping the plant phenotype. Efforts to develop new varieties characterized by higher yield and better wood quality will greatly benefit from recognizing and understanding the complex transcriptional network underlying wood development. The present study prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…Using pectin sensitive antibodies the absence of pectin in the secondary cell wall has been verified in pine xylem (Hafren et al, 2000) and stone cells of Norway spruce phloem (Kim and Daniel, 2017). In a very recent study on xylem cell wall formation in pioneer roots and stems of poplar pectins did not colocalize in lignified cell walls, but were found in primary tissues (Marzec-Schmidt et al, 2019). The role of acidic pectin in secondary cell wall formation of the nutshell is confirmed by our intense pectin band at 853-854 cm −1 in the July sample ( Figures 4F, 6D,E), which corresponds exactly to the same position as Polygalacturonic acid (Synytsya et al, 2003).…”
Section: Nut Shell: Secondary Cell Wall Formation and Lignificationmentioning
confidence: 95%
“…Using pectin sensitive antibodies the absence of pectin in the secondary cell wall has been verified in pine xylem (Hafren et al, 2000) and stone cells of Norway spruce phloem (Kim and Daniel, 2017). In a very recent study on xylem cell wall formation in pioneer roots and stems of poplar pectins did not colocalize in lignified cell walls, but were found in primary tissues (Marzec-Schmidt et al, 2019). The role of acidic pectin in secondary cell wall formation of the nutshell is confirmed by our intense pectin band at 853-854 cm −1 in the July sample ( Figures 4F, 6D,E), which corresponds exactly to the same position as Polygalacturonic acid (Synytsya et al, 2003).…”
Section: Nut Shell: Secondary Cell Wall Formation and Lignificationmentioning
confidence: 95%
“…While the role of ROS and antioxidants in the lignification of tracheary elements in cell cultures and their role in xylogenesis in developing stems are well known, information is lacking on their role in developmental processes in underground organs, such as pioneer roots. Only a few recent studies have compared pioneer root development to the ontogeny of stems [31,32]. In these studies, similarities were noted in cell wall development and the PCD of xylem cells, as well as organ-specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of this gene, which encodes a cell-wall localized protein, in isolated secondary xylem (SX) cells from stems, indicates that RCI3 may also be involved in PCD or/and lignification of xylem cells in Populus trichocarpa during xylogenesis. Our previous study [32] demonstrated that the expression of genes encoding enzymes involved in lignification increased during stem development and grouped in Cluster II. Similar results for all genes encoding PXs were obtained in the present study.…”
Section: Ros Are Involved In Xylem Developmentmentioning
confidence: 98%
See 2 more Smart Citations